The role of independent commissioner in moderate effect of financial performance and compensation on earnings management - Maloka, Lestari Dewi; Putri, I Gusti Ayu Made Asri Dwija (International research journal of management, IT and social sciences, 2021)
This study aims to determine the effect of financial performance and compensation on earnings management moderated by independent commissioners. This research was conducted in a manufacturing company listed on the Indonesia Stock Exchange in 2016-2020. The number of samples in this study were 26 companies with the number of observations obtained as many as 130 observations using the purposive sampling method. Data collection uses the documentation method. The data analysis technique used is moderated regression analysis. The results showed that financial performance had a positive effect on earnings management. Compensation has no effect on earnings management. Independent commissioners moderate the effect of financial performance on earnings management. Independent commissioners are unable to moderate the effect of compensation on earnings management. The theoretical implication of this research is to support agency theory and positive accounting theory, while practically this research can make a positive contribution to all parties, especially companies, management and the main users of financial statements.